A surrogate model for acid functional group conversion in alkyd reactor - Uzoh, Chigozie Francolins; Onukwuli, Okechukwu Dominic (South African journal of chemical engineering, 2016)
Due to lack of detailed kinetic model, the alkyd resin polymerization reactor problem has been a subject of extensive theoretical, simulation and experimental studies, given the demand of processes with better compromises between safety, productivity and quality, and the development of control methods. In this study, a novel linear integral kinetic model for the conversion of acid functional group have been developed for predicting the progress of the reaction in the alkyd batch reactor on the basis of empirical third-order rate model, wave propagation theory and discrete delayed measurements. The new approach when tested, using an alkyd reactor calibration problem was found to be much more reliable. The model was able to approximate the motion and the trajectory of the polyesterification reaction process such that the desired properties were kept within specification. •New model for acid functional group conversion in alkyd reactor is proposed.•Empirical third-order rate law and wave propagation theory were utilized.•The model was validated and verified under different alkyd reactions and realistic conditions.•The alkyd polyesterification variables curves converged excellently in the state space.